1998
DOI: 10.1088/0963-0252/7/4/013
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of RF plasma jet by optical methods

Abstract: An N 2 jet stream expanding from a radio-frequency discharge has been investigated by optical emission spectroscopy. The axial and lateral profiles of the expansion glow and the jet axial velocity have been measured by optical methods in order to infer the fluid-dynamic properties of the jet. The position of the shock wave is located at about 5 mm from the nozzle, and the stream velocity achieves a maximum of about 2 Mach in the supersonic region. Optical titration of N atoms and the analysis of emitting excit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…At longer discharge time the analysis of N 2 (C, v) distribution evidences that the excitation by electron impact from N 2 (A 3 Σ + u , v) starts competing with the electron impact from N 2 (X, v). At the end of the discharge pulse the excitation by energy pooling [6,7] of the N 2 (A 3 Σ + u , v) molecules compete with the two processes. Ground state vibrational distribution is no more Boltzmann-like and can be approximated by two or three temperature.…”
Section: Analysis Of N 2 (C V)mentioning
confidence: 99%
“…At longer discharge time the analysis of N 2 (C, v) distribution evidences that the excitation by electron impact from N 2 (A 3 Σ + u , v) starts competing with the electron impact from N 2 (X, v). At the end of the discharge pulse the excitation by energy pooling [6,7] of the N 2 (A 3 Σ + u , v) molecules compete with the two processes. Ground state vibrational distribution is no more Boltzmann-like and can be approximated by two or three temperature.…”
Section: Analysis Of N 2 (C V)mentioning
confidence: 99%
“…The formation of multiple expansion-compression waves in a supersonic free jet is well known, and several studies on the structure and applications of such jets are reported in the literature (Beylich 1999). In the case of a plasma jet at low power density the fluid-dynamic analysis of the expansion can be traced by optical emission (Robin, Vervish & Cheron 1994;Djakov, Enikov & Oliver 1997;De Benedictis et al 1998;Djakov et al 1999), but there are several problems that must be considered. The supersonic expansion of a molecular gas excited in a plasma chamber at relatively low pressure produces a rich flow of excited species whose energy relaxation takes place in a largely inhomogeneous fluid-dynamic environment.…”
Section: Introductionmentioning
confidence: 99%
“…The supersonic expansion of a molecular gas excited in a plasma chamber at relatively low pressure produces a rich flow of excited species whose energy relaxation takes place in a largely inhomogeneous fluid-dynamic environment. All the typical phenomena of an early afterglow (De Benedictis & Dilecce 1995;De Benedictis, Dilecce & Simek 1999b) can then contribute to the light emission from a plasma jet (De Benedictis et al 1998). Moreover the coupling between the relaxation kinetics of excited species and fluid dynamics must be considered.…”
Section: Introductionmentioning
confidence: 99%
“…[91][92][93][94][95] Major statistical distributions are considered for different internal degrees of freedom of atoms and molecules in quasiequilibrium and strongly nonequilibrium plasmas, including nonequilibrium statistics of vibrationally excited molecules, and Treanor distribution. [96][97][98][99][100] Principal thermodynamic functions of thermal plasma systems relevant to thermal plasma-medical devices are often introduced in the literature.…”
Section: B Quasiequilibrium and Nonequilibrium Plasmas: Statistics Amentioning
confidence: 99%